Retrospective Study: Oral Medications for Atopic Dermatitis - Yuri Widia; Marsoedi Hutomo (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disease, characterized by recurrent itch. The prevalence of AD in children is 10-20%, while in adults is as many as 1-3%. Several factors are proposed to play role in the pathogenesis of AD as well as genetics, immunological, and environmental factors. There are recent advances in the management of the AD but still not fully satisfactory. Purpose: To evaluate oral medications for AD to improve patient's care in the future. Methods: Retrospective study performed in Allergy Immunology Division of Dermatology and Venereology Outpatient Clinic Dr. Soetomo th stGeneral Hospital within January 1 2009 until December 31 2011. Data was collected from medical records. Results: There were 11.7% AD patients who received oral treatment. The most antihistamine given was mebhydrolin napadisilat in 51.5% of patients. The most corticosteroids given was dexamethasone in 33.6% patients. Dexamethasone was given in tapering off in 7.9% patients. The most oral antibiotics given was erythromycin in 4.8% patients and cloxacillin in 0.3% patients. Conclusions: Oral medications mostly used in AD was antihistamine. Some patients were also given corticosteroids. Antibiotics were used if secondary bacterial infection was assessed.Key words: atopic dermatitis, retrospective study, oral medications.